Characteristics, outcomes, and risk factors for in-hospital mortality of COVID-19 patients: A retrospective study in Thailand - Naorungroj, Thummaporn; Viarasilpa, Tanuwong; Tongyoo, Surat; Detkaew, Aeckapholpholladet; Pinpak, Thanchanok; Wimolwattanaphan, Rawish; Ratanarat, Ranistha; Promsin, Panuwat; Thamrongpiroj, Preecha; Phumpichet, Akekarin; Permpikul, Chairat (Frontiers in Medicine, 2023)
Introduction: Data on the characteristics and outcomes of patients hospitalized for Coronavirus Disease 2019 (COVID-19) in Thailand are limited. Objective: To determined characteristics and outcomes and identify risk factors for hospital mortality for hospitalized patients with COVID-19. Methods: We retrospectively reviewed the medical records of patients who had COVID-19 infection and were admitted to the cohort ward or intensive care units at Siriraj Hospital between January 2020 and December 2021. Results: Of the 2,430 patients included in this study, 229 (9.4%) died; the mean age was 54 years, 40% were men, 81% had at least one comorbidity and 13% required intensive care unit (ICU). Favipiravir (86%) was the main antiviral treatment. Corticosteroids and rescue anti-inflammatory therapy were used in 74% and 6%, respectively. Admission to the ICU was the only factor associated with reduced mortality (odds ratio [OR] 0.01, 95% confidence interval [CI] 0.01-0.05, P<0.001), whereas older age (OR 14.3, 95%CI 5.76-35.54, P<0.001), high flow nasal cannula (HFNC; OR 9.2, 95% CI 3.9-21.6, P<0.001), mechanical ventilation (OR 269.39, 95%CI 3.6-2173.63, P<0.001), septic shock (OR 7.79, 95%CI, 2.01-30.18, P=0.003) and hydrocortisone treatment (OR 27.01, 95%CI 5.29-138.31, P<0.001) were factors associated with in-hospital mortality. Conclusions: The overall mortality of hospitalized patients with COVID-19 was 9%. The only factor associated with reduced mortality was admission to the ICU. Therefore, appropriate selection of patients for admission to the ICU, strategies to limit disease progression and prevent intubation, and early detection and prompt treatment of nosocomial infection can improve survival in these patients.